Inside and outside of the imperial archives: the memory of the frontier - Buzov, Snježana (2007)
So far, most of the research of the Ottoman frontiers has been conducted by focusing on the documents preserved in the central imperial archives in Istanbul. The study of area of Triplex Confinium (the borderlands between the Ottoman and Habsburg Empire and the Venetian Republic) offers a variety of venues for the research of the local aspects of the Ottoman frontier(s). Central archives and collections that cover the frontier affairs through documents of correspondence, registers of the fortifications and garrisons, the affairs of the frontiers as reflected through sultanic decrees, and the representations of the events and developments on the frontier in various historical genres and geographical works. The local memory of the Ottoman frontier comes down to us through a variety of materials, some preserved in ordered provincial archives and registrars of the states involved, some representing oral, folk memory, and some observations and memory of particular groups in the frontier. The local materials are also recorded in a number of languages. Aside from the importance of the work and role of local dragoman (translators) offices that facilitated the communication between local Ottoman and Venetian authorities and rendered Ottoman documents in Latin and Italian, the representations and descriptions of the Ottoman governance and military power in the area were produced by local authors in all languages spoken or used by local population. The strong interest for Ottomans and Ottoman affairs among the local dignitaries, and local population resulted in a variety of literary works, and political pamphlets. While recently, within the international research project “ Triplex Confinium” a number of these works have been subject of scholarly discussion, The main difference between the memory of the frontier preserved in central imperial archives and that of the provincial archives and local literary production lies exactly in the potential of the latter provide an insight and also reframe the issues raised by this workshop. There, members of the Ottoman garrisons and provincial administrators emerge as a strong local factor rather than mere representatives of the Ottoman state. Their official role, their relationship with the government in Constantinople, and particularly their interaction with local population and local Venetian and Austrian authorities was determined by the frontier codes as much as by the conditions of their appointment. During most of the early modern period the slave trade was largely replaced (with exception of the periods of military conflict) by the practice of taking captives for the purpose of collecting ransom on the other side of the border. Similarly, the Ottoman trade in the border region relied heavily on the Ottoman outposts, mainly on Venetian territory, through the Ottoman iskeles in coastal towns. While the major routes of Ottoman international trade were directed to Venice and Dubrovnik, the coastal iskeles (with one exception of a relatively short period of the development of large scale trade through the iskele in Split) served the needs of daily trade for local Ottoman population.